Evolution of a transboundary landscape approach in the Hindu Kush Himalaya: Key learnings from the Kangchenjunga Landscape - Janita Gurung; Nakul Chettri; Eklabya Sharma; Wu Ning; Ram P. Chaudhary; Hemant K. Badola; Sonam Wangchuk; Yadav Uprety; Kailash S. Gaira; Namgay Bidha; Karma Phuntsho; Kabir Uddin; et al. (Global Ecology and Conservation, 2019)
The transboundary landscape approach builds on principles of integrated social-ecological systems with conservation and development perspectives at a transboundary level. The evolution of one such transboundary landscape in the Hindu Kush Himalaya (HKH) from the 1990's to the present is discussed through a phase-wise process. Both global and regional discourses have been influential in designing the transboundary Kangchenjunga Landscape which is shared by Bhutan, India and Nepal. The 25,085 sq.km landscape ranges in elevation from 40 to 8,586 m asl and is home to more than seven million people, while hosting more than 4,500 species of plants and at least 169 mammal and 618 bird species. With the aim of conserving and managing the landscape for sustained ecosystem services that ultimately contribute to the livelihoods of the women and men residing therein, the Kangchenjunga Landscape Conservation and Development Initiative was implemented since 2016. Lessons from the Kangchenjunga Landscape indicate that participatory and iterative boundary delineation, transboundary cooperation, identification of a lead institution, ensuring the global-local-global feedback cycle, and regional data sharing are key components for implementing transboundary landscape programmes in the region. Keywords: Landscape approach, Ecosystem management, Participatory planning, Regional cooperation, Theory of change